Promoting Biodiversity Conservation Requires a Better Understanding of the Relationships Between Ecosystem Services and Multiple Biodiversity Dimensions - Wu, Shuyao; Chen, Yuqing; Hao, Chaozhi; Liu, Kaidi; Zhang, Wentao; Zhang, Linbo (Frontiers in Ecology and Evolution, 2022)
In order to reverse the global trend of biodiversity loss, the concept of ecosystem services has been widely applied to make policymakers and the general public realize that conserving biodiversity possesses both intrinsic and utilitarian values. However, to achieve this goal, it is necessary to first have a clear understanding of the relationships between biodiversity and ecosystem services (BES). To advance our understanding of this issue, we first reviewed the major progress in current BES studies, with an emphasis on three biodiversity dimensions (i.e., taxonomic diversity, functional diversity and ecosystem diversity). Based on the findings, we then propose three research topics as future directions: 1) more direct and explicit studies on the effects of different dimensions of biodiversity on various ecosystem service types; 2) developing a biodiversity-based understanding of the formation of ecosystem services; 3) creation of science-based ecosystem management plans and policies that can maximize synergies between biodiversity conservation and ecosystem service enhancement. By conducting such research, we will be able to not only further understand the complex relationships between biodiversity and ecosystem services but also better promote the concept of ecosystem services for more successful biodiversity conservation in the future.